Experimental investigation of sulfur distribution and yields of liquid fuel and petroleum coke produced by thermal cracking of vacuum residues. (January 2023) - Safiri, Amir; Ivakpour, Javad; Yazdani, Esmaeil; Mohammadi, Amir H.
Abstract: In the present work, an experimental study was conducted to investigate the sulfur distribution in the products during thermal degradation of vacuum residues at different operating conditions. In this regard, three vacuum residues with different sulfur contents were selected. The effects of main operating conditions such as pressure and temperature on products yields and properties were studied. The results show that for sulfur distribution, which is indicated as the ratio of the amount of sulfur in each product to the initial mass of sulfur in the feed, increasing temperature will be followed by increased sulfur distribution in liquid fuel and reduced sulfur distribution in petroleum coke. Furthermore, effects of reaction temperature on yields of light coker gasoil (150–350 °C) as well as heavy coker gasoil (350–500 °C), as the dominant fractions of thermal cracking products, were evaluated using simulated distillation method. Graphical abstract: Image 1